School Feeding and Girls’ Enrollment: The Effects of Alternative Implementation Modalities in Low-Income Settings in Sub-Saharan Africa - Gelli, Aulo (Frontiers in Public Health, 2015)
Background: School feeding interventions are implemented in nearly every country in the world, with the potential to support the education, health and nutrition of school children. There is little evidence to show that different school feeding modalities have different effects. Objective: To examine the influence of different school feeding modalities on primary school enrolment, particularly for girls, in 32 countries across sub-Saharan Africa. Methods: An observational study involving a meta-analysis of survey data was developed to examine programme effect. Schools were divided by type and length of program: those with existing programs, those that had had school feeding for less than one year, and a counterfactual including schools without a programme. The intervention consisted of two different types of school feeding: onsite meals alone or onsite meals plus take-home rations. Changes in enrolment over a one-year period were used to assess effects of school feeding. To control for pre-programme characteristics, data on covariates were also examined. Using this design a comparison of enrolment levels was made between the types of treatment schools and controls schools during the period school feeding was first introduced. Standard multiple regression models were used to analyse programme effect. Results: School feeding was found to have statistically significant increases in enrolment, with effect size of about 10 percent. The changes on enrolment varied by modality of school feeding provision and by gender, with onsite meals appearing to have stronger effects in the first year of treatment in the lower primary grades, and onsite combined with take-home rations also being effective post-year 1, particularly for girls that were receiving the extra take-home rations. Conclusions: School feeding programmes had a positive impact on school enrolment. The operational nature of the survey data used in the meta-analysis, however, limits the robustness of the findings.